Beatific Afterlife in Ancient Israel and in the Ancient Near East - Spronk, Klaas (1986)
spez. 86-236: Conceptions of Beatific Afterlife in the Ancient Near East: Egypt. Mesopotamia. Asia Minor. Greece. Syria and Palestine (except Israel).